Fluorescence and diffuse reflectance spectroscopy for early cancer detection using a new strategy towards the development of a miniaturized system - Ferreira, D. S. (2010)
This paper describes the design of a miniature, cost-effective spectroscopy system for assessing tissue biochemical and morphological information using a few wavelengths. This instrument will integrate thin-film optical filters and silicon photodiodes, avoiding the use of a spectrograph and optical fibers. The components in the set-up design are described. The feasibility of using only 16 wavelengths to accurately extract tissue properties is confirmed on physical tissue models. Also, the suitable spectral performance of several optical filters for the selection of these wavelengths is demonstrated. The small size of this device will enable implementation in an endoscopic capsule.